Answer :
3y + 9 = 3y
9 = 3y - 3y
9 = 0 (no solution)...means no matter what number u put in for y, it will not come out equal
3y + 9 = 10
3y = 10 - 9
3y = 1
y = 1/3 (one solution)
3y + 9 = 3(y + 3)
3y + 9 = 3y + 9
3y - 3y = 9 - 9
0 = 0 (infinite solutions)...means no matter what number u put it for y, it will always come out equal
9 = 3y - 3y
9 = 0 (no solution)...means no matter what number u put in for y, it will not come out equal
3y + 9 = 10
3y = 10 - 9
3y = 1
y = 1/3 (one solution)
3y + 9 = 3(y + 3)
3y + 9 = 3y + 9
3y - 3y = 9 - 9
0 = 0 (infinite solutions)...means no matter what number u put it for y, it will always come out equal